Occurrence and genetic diversity of the Plasmopara halstedii virus in sunflower downy mildew populations of the world. Issue 2 (March 2015) - Grasse, Wolfgang; Spring, Otmar
Abstract: Plasmopara halstedii virus (PhV) is a ss(+)RNA virus that exclusively occurs in the sunflower downy mildew pathogen Plasmopara halstedii, a biotrophic oomycete of severe economic impact. The virus origin and its genomic variability are unknown. A PCR-based screening of 128 samples of P. halstedii from five continents and up to 40 y old was conducted. PhV RNA was found in over 90 % of the isolates with no correlation to geographic origin or pathotype of its host. Sequence analyses of the two open reading frames (ORFs) revealed only 18 single nucleotide polymorphisms (SNPs) in 3873 nucleotides. The SNPs had no recognizable effect on the two encoded virus proteins. In 398 nucleotides of the untranslated regions (UTRs) of the RNA 2 strand eight additional SNPs and one short deletion was found. Modelling experiments revealed no effects of these variations on the secondary structure of the RNA. The results showed the presence of PhV in P. halstedii isolates of global origin and the existence of the virus since more than 40 y. The virus genome revealed a surprisingly low variation in both coding and noncoding parts. No sequence differences were correlated with host pathotype or geographic populations of the oomycete. Highlights: PCR-based screening showed occurrence of mycovirus PhV in more than 90 % of host samples. No correlation of PhV presence with host pathotype, sample origin or age was observed. Genetic diversity of PhV was extremely low in ORFs as well as in UTRs.